Pengenalan Aplikasi Blooket Sebagai Media Pembelajaran Di Sma Teruna Bakti Waena Jayapura - Sinaga, Ego Srivajawaty; Hubertus Ngaderman; Kezia Noviani Anou; Bangkit Sudrajad; Daniel Napitupulu; Benny Abraham Bungasalu (LPPM UMRI, 2025)
Conventional learning makes students easily bored so that the development of information and communication technology has had a positive impact on progress in the world of education such as the internet and e-learning, making learning possible from anywhere. Educational games can be used as a fun and interactive learning media. One of the educational games is blooket. The purpose of this service activity is to make students more enthusiastic in learning physics and proficient in using the blooket application. The methods used are lectures and practices. The results obtained after carrying out this service activity students prefer educational games compared to quizzes that are done conventionally and students can use the blooket application well.